2018
DOI: 10.7762/cnr.2018.7.4.229
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Alzheimer's Disease: Mechanisms and Nutritional Aspects

Abstract: Blood glucose homeostasis is well maintained by coordinated control of various hormones including insulin and glucagon as well as cytokines under normal conditions. However, chronic exposure to diabetic environment with high fat/high sugar diets and physical/mental stress can cause hyperglycemia, one of main characteristics of insulin resistance, metabolic syndrome, and diabetes. Hyperglycemia impairs organogenesis and induces organ abnormalities such as cardiac defect in utero. It is a risk factor for the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 71 publications
(84 reference statements)
2
95
1
5
Order By: Relevance
“…The inhibition of cholinesterases, namely acetylcholinesterase and butyrylcholinesterase, remains the main focus for the management of Alzheimer's disease. Besides, an increasing number of publications and clinical studies substantiates that Alzheimer's disease and type 2 diabetes might share some pathophysiological similarities [42,43]. As such, type 2 diabetes has been identified as a risk factor for Alzheimer's disease based on multiple connections [44].…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of cholinesterases, namely acetylcholinesterase and butyrylcholinesterase, remains the main focus for the management of Alzheimer's disease. Besides, an increasing number of publications and clinical studies substantiates that Alzheimer's disease and type 2 diabetes might share some pathophysiological similarities [42,43]. As such, type 2 diabetes has been identified as a risk factor for Alzheimer's disease based on multiple connections [44].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, adopting this fat-rich dietary pattern can lead to metabolic disorders such as obesity or Type 2 Diabetes Mellitus (T2DM), these latter being associated with a higher risk of developing dementia in later life [9,10].Nutritional strategies represent a promising area to prevent neurocognitive impairments and subsequent dementia. While the precise mechanisms underlying the relationships between these dietary habits on age-related cognitive disorders are not yet completely understood (for instance, inflammatory pathways, vascular factors, oxidative stress or amyloidogenesis [11][12][13][14]), we suggest that the activation of the innate immune system by endotoxins-which are still poorly described-could be considered as one potential cellular mechanism involved in these relationships.Endotoxins (Lipopolysaccharides, LPS), a major component of the outer membrane of Gram-negative bacteria, are now well as contributors to the inflammation [15]. Although LPS may originate from skin and mucous membranes or local sites of bacterial infection for instance, the gut microbiota is considered the main natural reservoir of pro-inflammatory endotoxins in the body [16].…”
mentioning
confidence: 89%
“…Nutritional strategies represent a promising area to prevent neurocognitive impairments and subsequent dementia. While the precise mechanisms underlying the relationships between these dietary habits on age-related cognitive disorders are not yet completely understood (for instance, inflammatory pathways, vascular factors, oxidative stress or amyloidogenesis [11][12][13][14]), we suggest that the activation of the innate immune system by endotoxins-which are still poorly described-could be considered as one potential cellular mechanism involved in these relationships.…”
mentioning
confidence: 89%
“…Streptozotocin (STZ), a naturally occurring alkylating antineoplastic agent that is particularly toxic to the insulin‐producing β cells of the pancreas in mammals, is structurally similar to glucose and N ‐acetyl glucosamine and can induce peripheral insulin resistance in animals by inhibiting N‐acetyl amino glycosidase enzymes and destroying islet β cells . It has been reported that the cognitive decline of diabetic patients complicated with AD is significantly severer than patients who only suffer from the pathologies of AD . In addition, the dysfunctions of insulin/insulin‐like growth factor‐1 signal pathway may cause neurodegeneration in center nerve system .…”
Section: Metabolic Damage Modelsmentioning
confidence: 99%
“…44 It has been reported that the cognitive decline of diabetic patients complicated with AD is significantly severer than patients who only suffer from the pathologies of AD. 45 In addition, the dysfunctions of insulin/insulin-like growth factor-1 signal pathway may cause neurodegeneration in center nerve system. 46 STZ simulates characteristic pathology of sAD such as lowed glucose metabolism, glycogen synthase kinase-3β activation, Aβ deposition, Tau hyperphosphorylation, synaptic dysfunction, and neuronal apoptosis.…”
Section: Streptozotocin-induced Ad Animal Modelmentioning
confidence: 99%